2013
DOI: 10.1681/asn.2012040355
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-A Receptor Antagonism Modifies Cardiovascular Risk Factors in CKD

Abstract: Arterial stiffness and impaired nitric oxide (NO) bioavailability contribute to the high risk for cardiovascular disease in CKD. Both asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO production, and endothelin-1 (ET-1) oppose the actions of NO, suggesting that ET-1 receptor antagonists may have a role in cardiovascular protection in CKD. We conducted a randomized, double-blind, three-way crossover study in 27 patients with proteinuric CKD to compare the effects of the ET A receptor antagonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
0
19
1
Order By: Relevance
“…However, we are aware that the dose selected was relatively higher than previously tested doses in patients. 42 We did not observe any adverse effects (e.g., fluid retention assessed by differences in body weight between groups after treatments) frequently observed in patients, which may have reflected species differences.…”
Section: Discussionmentioning
confidence: 49%
“…However, we are aware that the dose selected was relatively higher than previously tested doses in patients. 42 We did not observe any adverse effects (e.g., fluid retention assessed by differences in body weight between groups after treatments) frequently observed in patients, which may have reflected species differences.…”
Section: Discussionmentioning
confidence: 49%
“…7 A few studies have examined the 24-hour variation of BP in CKD. [8][9][10] They suggest that not only is nondipping a feature of CKD but also as glomerular filtration rate declines, reverse dipping (nighttime BP readings that are higher than those during the Recently, we showed that chronic selective ET A receptor antagonism-using the orally active drug sitaxentan-reduces BP, proteinuria, and more novel cardiovascular disease (CVD) risk factors including arterial stiffness, uric acid, and asymmetrical dimethylarginine in patients with proteinuric CKD, 18,19 effects that are potentially renoprotective. Here, we present data from 3 studies: in the first, we examined the nocturnal dip in both ambulatory BP and arterial stiffness in patients with CKD and controls.…”
mentioning
confidence: 99%
“…Recently, we showed that chronic selective ET A receptor antagonism-using the orally active drug sitaxentan-reduces BP, proteinuria, and more novel cardiovascular disease (CVD) risk factors including arterial stiffness, uric acid, and asymmetrical dimethylarginine in patients with proteinuric CKD, 18,19 effects that are potentially renoprotective. Here, we present data from 3 studies: in the first, we examined the nocturnal dip in both ambulatory BP and arterial stiffness in patients with CKD and controls.…”
mentioning
confidence: 99%
“…These additional effects may, in theory, confer improved cardiovascular and renal protection. 90,116 With regard to the safety data from this study, in contrast to the effects of other ERAs in diabetic nephropathy, it is worth noting that there was no evidence of fluid retention within this cohort. Sitaxentan has been shown to have no functional effect on ET B in vivo in human beings 117 and these observations would be consistent with a role for ET B in fluid accumulation.…”
Section: Clinical Studiesmentioning
confidence: 80%
“…In patients with CKD, however, ET A activity appears increased, with a preferential effect on the efferent arteriole, raising the possibility that ET-1 promotes hyperfiltration in CKD. The vasoconstrictor effect of BQ788 in both health and disease suggests that ET B plays an important role in maintaining basal systemic 90,115,116 Sitaxentan therapy also improved markers of arterial stiffness, improved nocturnal BP dip, and reduced plasma asymmetric dimethylarginine (ADMA) and uric acid and renal vascular tone, and indicates that its blockade in CKD may have negative consequences on both systemic BP and renal blood flow. 111 A further acute study, using BQ123, in 22 patients with nondiabetic proteinuric CKD found that BQ123 caused significant reductions in BP and arterial stiffness and increased renal blood flow while causing a decrease in proteinuria of approximately 30%.…”
Section: Clinical Studiesmentioning
confidence: 99%